Religion and rituals as coping strategies during war - VEBEROVA, Anna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. This article explores religion and rituals as coping strategies during wartime. By analyzing contemporary studies and theoretical models in neuropsychology, it investigates mechanisms for overcoming stress through faith and rituals. The study aims to integrate existing knowledge to form a comprehensive understanding of the role of religion and rituals in alleviating chronic stress.Methods. This is a classical theoretical study based on an analysis of contemporary literature in neuropsychology, the psychology of coping strategies, and studies on social and religious phenomena under crisis conditions. The primary sources include peer-reviewed scientific publications, monographs, findings from previous empirical research, as well as international and Ukrainian reports on the psychological state of the population during wartime.Results. The article demonstrates that religion and rituals serve as powerful coping strategies during war. Religion provides a sense of meaning, rituals establish structure and an illusion of control over the situation, and social support (whether from family, friends, volunteer communities, or religious organizations) fosters emotional stability. These adaptive mechanisms help manage chronic stress, reduce anxiety levels, and strengthen mental health overall. However, the lack of comprehensive studies limits a full understanding of the scope and specifics of these strategies within Ukrainian society during the war.Conclusions. Wartime conditions compel individuals to seek adaptive mechanisms for preserving mental health. Religion, rituals, and social support play a crucial role in combating chronic stress. Nonetheless, there is a need for more extensive studies (potentially experimental ones) on coping strategies to develop effective approaches for supporting Ukrainian citizens under crisis conditions.
Keywords: coping strategies; religion; rituals; toxic resilience; stress; stress respons